African women and young people as agriculture service providers—business models, benefits, gaps and opportunities - Mariam Kadzamira; Florence Chege; Chubashini Suntharalingam; Mary Bundi; Linda Likoko; Deogratius Magero; Dannie Romney; Monica Kansiime; Joseph Mulema (CABI Agriculture and Bioscience)
Abstract We use a combination of a global desk review of the literature with information from an on-going action research in Kenya to provide insights into the main characteristics, benefits and shortfalls of business models for engaging women and young people in agricultural service provision in Africa. The findings demonstrate that the engagement of African women and young people in agricultural service provision is not a panacea to the challenges they face. However various business models have been successful in contributing to economic empowerment, to increasing entrepreneurial activities and to upskilling of women and young people engaged as service providers. Business models that are successful are place-based and people-focused, market-driven and focused on value chains. Challenges however abound due to various factors, hence for sustainability there is need for multi-sectoral inter-institutional collaboration that pulls in funding and which makes a case for private sector buy-in. Future research should focus on increasing the evidence base to understand if successes with inclusion of women and young people in agricultural service provision has an influence on emerging agricultural policy. Research should also rigorously assess the extent to which successful agricultural service provision business models are engendered, provide sufficient levels of renumeration and the extent to which they impact farmer outcomes.